2022
DOI: 10.4314/ahs.v22i4.74
|View full text |Cite
|
Sign up to set email alerts
|

The effectiveness of locally-prepared peritoneal dialysate in the management of children with acute kidney injury in a south-east Nigerian tertiary hospital

Abstract: Background: Peritoneal dialysis (PD) is the preferred mode of renal replacement therapy (RRT) in children with acute kidney injury (AKI). The gold standard remains the use of commercially-prepared PD fluid. In resource-poor nations, its availability and affordability remain a challenge.Aim: This study aims to report the effectiveness of locally-prepared PD fluid in the management of AKI in a south-east Nigerian tertiary hospital.Subjects and Methods: This was a retrospective study conducted at the paediatric w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(12 citation statements)
references
References 22 publications
0
0
0
Order By: Relevance
“…The study in Kano Nigeria [6] observed AGN as the most common AKI etiology requiring RRT and AGN was a prominent cause also found in other studies. [9,15,16] Haemolysis-associated hemoglobin cast nephropathy was documented in other studies [5,14]. Sepsis was the most common cause of AKI in RRT patients as observed in some other studies in Nigeria [8,10,[14][15][16] Ghana, [9] Pakistan [11], and Turkey [13] unlike in this index study where it constituted only 10% of cases and less prominent in other studies in Nigeria [5].…”
Section: Dialysis In Children South Southern Nigeriasupporting
confidence: 55%
See 4 more Smart Citations
“…The study in Kano Nigeria [6] observed AGN as the most common AKI etiology requiring RRT and AGN was a prominent cause also found in other studies. [9,15,16] Haemolysis-associated hemoglobin cast nephropathy was documented in other studies [5,14]. Sepsis was the most common cause of AKI in RRT patients as observed in some other studies in Nigeria [8,10,[14][15][16] Ghana, [9] Pakistan [11], and Turkey [13] unlike in this index study where it constituted only 10% of cases and less prominent in other studies in Nigeria [5].…”
Section: Dialysis In Children South Southern Nigeriasupporting
confidence: 55%
“…The outcome of the children with AKI who had acute dialysis had varied responses ranging from full recovery, inpatient mortality, and progression to ESRD requiring chronic dialysis to undetermined due to loss of follow-up [6,7,11,[14][15][16][17]. Pediatric patients with both AKI and CKD require RRT during their management.…”
Section: Online Firstmentioning
confidence: 99%
See 3 more Smart Citations